Penyuluhan Berbasis Leaflet dalam Persiapan Persalinan: Penyuluhan Berbasis Leaflet dalam Persiapan Persalinan - Apriyani, Magdalena Tri Putri - (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2023)
Introduction Reducing MMR and IMR is one of the indicators in the third Goal of the SDGs program which is a continuation of the MDGs. One of the SDGs targets is to reduce MMR to 70 per 100,000 live births by 2030 and reduce IMR to 16 per 1000 live births by 2024. The Purpose is to increase the knowledge of pregnant women about discomfort in pregnancy and how to deal with it. Methods In this community service the researchers focused on providing information education to pregnant women about discomfort in pregnant women with direct counseling methods and giving pre-tests and post-tests to these pregnant women, for those who could answer and were actively given souvenirs. Implementation on December 19, 2023 in Ciawi Bogor. Keywords : Leaflet, Labor Preparation